2013
DOI: 10.1136/bmjqs-2013-002118
|View full text |Cite
|
Sign up to set email alerts
|

Are interventions to reduce interruptions and errors during medication administration effective?: a systematic review

Abstract: BackgroundMedication administration errors are frequent and lead to patient harm. Interruptions during medication administration have been implicated as a potential contributory factor.ObjectiveTo assess evidence of the effectiveness of interventions aimed at reducing interruptions during medication administration on interruption and medication administration error rates.MethodsIn September 2012 we searched MEDLINE, EMBASE, CINAHL, PsycINFO, Cochrane Effective Practice and Organisation of Care Group reviews, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
146
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(153 citation statements)
references
References 41 publications
(122 reference statements)
1
146
1
5
Order By: Relevance
“…A recent review of studies that have tested interventions to reduce interruptions and, by implication, to reduce medication administration errors, has noted that there is only weak evidence that such interventions are effective (Raban & Westbrook, 2014). In this section we highlight a "multi-intervention" study by Tomietto, Sartor, Mazzocoli, and Palese (2012), which led to conflicting outcomes, a medication administration accuracy study by Kliger, Singer, Hoffman, and O'Neil (2012) that included minimising interruptions and distractions, and an early study of interventions by Pape (2003) to reduce interruptions.…”
Section: Intervention Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review of studies that have tested interventions to reduce interruptions and, by implication, to reduce medication administration errors, has noted that there is only weak evidence that such interventions are effective (Raban & Westbrook, 2014). In this section we highlight a "multi-intervention" study by Tomietto, Sartor, Mazzocoli, and Palese (2012), which led to conflicting outcomes, a medication administration accuracy study by Kliger, Singer, Hoffman, and O'Neil (2012) that included minimising interruptions and distractions, and an early study of interventions by Pape (2003) to reduce interruptions.…”
Section: Intervention Studiesmentioning
confidence: 99%
“…As noted by Raban and Westbrook (2014), almost all intervention studies (with the exception of Pape, 2003) have been quasi-experiments with a pre-post design. Assigning participants at random to conditions that are run in parallel with each other is impractical, due to the need to keep work practices consistent within hospital units.…”
Section: Intervention Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential aspects of the sterile cockpit concept include eliminating interruptions, prohibiting communication unrelated to critical tasks, and maximizing teamwork and coordination during high-risk activities. 21,22 The majority of published clinical initiatives to limit interruptions during medication administration are nurse-led quality improvement projects involving implementation of a set of strategies to limit interruptions ( Table 1). The goal of these initiatives is to provide nurses with time to remain focused and undisturbed while preparing and administering medications.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Strategies to reduce distractions, such as posting "Do Not Disturb" signs, or vests worn by nurses to indicate they are administering medications, have had mixed results. [2][3][4] Moreover, to ensure patient safety, it is undesirable to eliminate all interruptions and distractions. In their review of the subject, Hayes et al identified "the need for the development of sustainable programmes that include high quality learning experiences that teach interruption management to undergraduate nurses in a safe environment" (p. 1063).…”
Section: Introductionmentioning
confidence: 99%